Upaya Meningkatkan Hasil Belajar Keterampilan Manipulatif Lengan pada Pembelajaran Model Pendidikan Gerak Berformat Permainan - Rahayu, Risma Jati (TEGAR: Journal of Teaching Physical Education in Elementary School, 2019)
This research was motivated by the fact that so many children in elementary schools having low manipulative skills, which can be related to teacher's low attention to these skills. This study was directed to improve arm manipulation skills by using a game format on movement education model, using a classroom action research. GPAI (Games Performance Assessment Instrument) and field notes were employed as the instrument. The samples of this study were 34 student, consist of (17 boys and 17 girls). There was 9,54% improvement that can be detected from the results of the pre test to the end of the cycle. It can be concluded that the game format of movement education model can improve arm manipulation skills of 4th grade students. The implication of this research is that movement education models should be actively occupied in the PE lesson in elementary schools. AbstrakPenelitian ini dimotivasi oleh rendahnya keterampilan manipulatif siswa di sekolah dasar, yang menunjukkan kurangnya perhatian guru pada keterampilan tersebut. Penelitian ini diarahkan untuk meningkatkan keterampilan manipulatif lengan dengan menerapkan model pendidikan gerak berformat permainan. Metode yang digunakan dalam penelitian ini adalah penelitian tindakan kelas dengan instrumen GPAI (Games Perfomance Assesment Instrument) dan catatan lapangan. Partisipan penelitian ini adalah 34 siswa, terdiri dari (17 laki-laki dan 17 perempuan). Terdapat peningkatan 9,54% dari hasil pre test hingga siklus 2 tindakan 2. Dengan demikian dapat disimpulkan bahwa pembelajaran model pendidikan gerak berformat permainan dapat meningkatkan keterampilan manipulatif lengan terhadap siswa kelas 4.